The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pssb.201046463
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition in lanthanum gallate as studied by Raman and X‐ray diffraction measurements

Abstract: Lanthanum gallate (LaGaO 3 ) is known to undergo orthorhombic to rhombohedral first order phase transition at 150 8C. In this article we have shown that by introducing 2% La deficiency in the system, coexistence of above two phases can be obtained at lower temperature and a complete phase transition occurs at 200 8C. The evolution of structural parameters of the system with temperature is reported from X-ray diffraction measurements and Rietveld analysis of the diffraction patterns. The change in local octahed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(74 reference statements)
0
7
0
1
Order By: Relevance
“…The sequence of structural phase transitions from a low temperature phase in Pbnm to a higher temperature phase in F32=n is not without precedent, having being found in BaCeO 3 [25,26] and BaPrO 3 [27], but in both of these cases, it occurs via a continuous phase transition to an intermediate phase in space group Ibnn. Despite the large number of crystallographic studies of the Pbnm to F32=n phase transition in LaGaO 3 [1,[7][8][9]11,12,[14][15][16][17][18][19] none have been carried out in sufficiently fine enough temperature intervals to ascertain whether an intermediate phase exists in this system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of structural phase transitions from a low temperature phase in Pbnm to a higher temperature phase in F32=n is not without precedent, having being found in BaCeO 3 [25,26] and BaPrO 3 [27], but in both of these cases, it occurs via a continuous phase transition to an intermediate phase in space group Ibnn. Despite the large number of crystallographic studies of the Pbnm to F32=n phase transition in LaGaO 3 [1,[7][8][9]11,12,[14][15][16][17][18][19] none have been carried out in sufficiently fine enough temperature intervals to ascertain whether an intermediate phase exists in this system.…”
Section: Introductionmentioning
confidence: 99%
“…The first order structural phase transition in LaGaO 3 , from orthorhombic Pbnm (Pnma in standard setting) to rhombohedral F32=n (R3c in standard setting) has been the subject of numerous studies in recent years [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We make this choice of the rhombohedral space group setting as it allows ease of comparison with both the aristotype and hettotype phases of perovskitestructured phases that is not immediately apparent from the more commonly used primitive rhombohedral, or triply-primitive hexagonal settings.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] As a case, the orthorhombic (Pnma) LaGaO3 transforms to a rhombohedral (R3 � c) structure at 150°C as well as at 2.5 GPa. 7,8 On the contrary, the cubic perovskite-type fluorides BaLiF3 and KMgF3 remain stable up to significantly higher pressure, viz > 40 GPa. 9, 10 4 On the other hand, although a number of structural studies on orthorhombic perovskites have been reported in the literature, the structural transitions are not unique.…”
Section: Introductionmentioning
confidence: 99%
“…In the present case the tilt angles were calculated from the observed Sc-O-Sc bond angles according to the methods reported in the literature. 27,28 The tilt angles θ, φ and ϕ for ambient temperature orthorhombic CeScO 3 are 18.3°, 8.7°, and 20.2°, respectively. The representative tilt angles ϕ about the (111) p axis for PrScO 3 , Pr 0.75 Ce 0.25 ScO 3 , Pr 0.5 Ce 0.5 ScO 3 , Pr 0.25 Ce 0.75 ScO 3 and CeScO 3 were 19.9°, 20.6°, 19.8°, 19.3°and 20.2°, respectively.…”
Section: Resultsmentioning
confidence: 99%